1998
DOI: 10.2134/agronj1998.00021962009000050011x
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated Corn Yield and Nitrogen Accumulation Response in a Comparison of No‐till and Conventional Till: Tillage and Surface‐Residue Variables

Abstract: Comparisons between no‐till and conventional‐till management are often confounded by variation in both tillage and residue placement. The objective of this research was to separate the tillage variable from the surface‐residue variable associated with no‐till and conventional‐till management comparisons in irrigated continuous corn (Zea mays L.) production. Two Nebraska locations (Mead and Clay Center) with differences in soil types and climate were selected. Four tillage‐residue treatments [NT‐NR (no‐till, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0
11

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 16 publications
7
45
0
11
Order By: Relevance
“…Method of sowing is the major factor which is responsible for soil moisture storage, judicious use of fertilizer, water, good crop stand and better crop growth. Simes et al, (1998) suggested that pre-plant tillage may be necessary to optimize grain yield and reported lower continuous corn yields with no tillage compared with conventional tillage. The conventional flat planting is the common practice of raising crops in India but this practice has resulted in the degradation and inefficient use of basic resources and various inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Method of sowing is the major factor which is responsible for soil moisture storage, judicious use of fertilizer, water, good crop stand and better crop growth. Simes et al, (1998) suggested that pre-plant tillage may be necessary to optimize grain yield and reported lower continuous corn yields with no tillage compared with conventional tillage. The conventional flat planting is the common practice of raising crops in India but this practice has resulted in the degradation and inefficient use of basic resources and various inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo MAR et al (2003), para se obter a máxima eficiência do fertilizante nitrogenado é importante determinar as épocas em que esse nutriente é mais exigido pelas plantas, permitindo assim, corrigir as deficiências que possam ocorrer no desenvolvimento da cultura. A eficiência da adubação Nascimento et al (2012) nitrogenada é dependente de condições climáticas, tipo de solo, acidez, conteúdo de argila, cultivares, cultura antecessora, distribuição de chuvas, níveis de fertilização nitrogenada e sua interação com outros nutrientes (SIMS et al, 1998).…”
Section: Introductionunclassified
“…Verifica-se que, quando as doses de N adicionadas são maiores que a necessidade das culturas, o rendimento vegetal não tem sido afetado pelo método de aplicação ou pela presença ou não de palha (Sims et al, 1998) porque as perdas de N, nesse caso, são inferiores ao excesso disponível.…”
Section: Experimento De Imobilizaçãounclassified
“…Sendo assim, as recomendações de fertilização nitrogenada são baseadas em experimentos regionais, cujas respostas variam com o pH, quantidade de matéria orgânica (CFS/RS-SC, 1995), tipo de preparo (Sims et al, 1998) e características químicas do solo (Howard & Essington, 1998), além do manejo da cobertura vegetal morta (Sims et al, 1998;Vaughan & Evanylo, 1998), do tipo (Aulakh et al, 2000, da época (Basso & Ceretta, 2000) e da forma de aplicação dos fertilizantes nitrogenados (Howard & Essigton, 1998;Sims et al, 1998).…”
Section: Introductionunclassified